2023
DOI: 10.3390/nano13192693
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Dispersed Copper(II) Oxide Nanosuspensions as Precursor for Femtosecond Reductive Laser Sintering by High-Energy Ball Milling

Kay Bischoff,
Cemal Esen,
Ralf Hellmann

Abstract: This contribution demonstrates and discusses the preparation of finely dispersed copper(II) oxide nanosuspensions as precursors for reductive laser sintering (RLS). Since the presence of agglomerates interferes with the various RLS sub-processes, fine dispersion is required, and oversized particles must be identified by a measurement methodology. Aside from the established method of scanning electron microscopy for imaging individual dried particles, this work applies the holistic and statistically more signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Only when sufficiently diluted to a ratio of 1.33 or less, the PC has a high flowability immediately after shearing, so that the grooves formed during coating are smoothed out. Previous work [22] has shown, in connection with the presence of large agglomerates in the PC, that a homogeneous surface is urgently required in order to produce reproducible, homogeneous and defect-free Cu structures. Shestakov et al also showed in the context of RLS with deep eutectic solvents that the layer thickness of the PC has a significant influence on the laser-generated Cu structure [30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Only when sufficiently diluted to a ratio of 1.33 or less, the PC has a high flowability immediately after shearing, so that the grooves formed during coating are smoothed out. Previous work [22] has shown, in connection with the presence of large agglomerates in the PC, that a homogeneous surface is urgently required in order to produce reproducible, homogeneous and defect-free Cu structures. Shestakov et al also showed in the context of RLS with deep eutectic solvents that the layer thickness of the PC has a significant influence on the laser-generated Cu structure [30].…”
Section: Discussionmentioning
confidence: 99%
“…The results shown in this work deviate from previous observations and show that a homogeneous surface can only be formed when the particle content is reduced to about 50 wt%. In addition to the different coating technique, we presume that this is primarily due to the milling process, which is associated with highly dispersed PC [22]. The degassing of the PC also prevents the formation of fine air bubbles during the drying process of the PC layer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, selective surface activation induced by laser (SSAIL) is a prominent representative of the first group, and laser scribing is used for dielectric surface activation to facilitate further selective metallization. On the contrary in reductive laser sintering (rSLS), , lasers are directly employed for the chemical reduction of CuO nanoparticles (NPs), as well as for sintering these particles to form copper patterns . This approach has a great perspective for the fabrication of micro-thermocouples and tactile and electrochemical sensors based on copper, nickel, cobalt, and composite films. , …”
Section: Introductionmentioning
confidence: 99%